The effects of polyelectrolytes on the inhibition and aggregation of calcium oxalate crystallization - Akyol, E; Bozkurt, A; Öner, M (WILEY, 2006)
The influence of polyelectrolytes with different architecture on spontaneous batch crystallization of calcium oxalate was investigated. A series of acidic acrylate block copolymers were been made, by radical polymerization, with defined molecular weight and structure. Radical polymerization of acrylic acid (AA) was carried out in the presence of alpha-thiopolyethylene glycol monomethylether as a chain transfer agent to produce poly(ethylene glycolblockacrylic acid) copolymers. Poly(ethylene glycol) (PEG) block length in the copolymers was controlled by using three different molecular weight chain transfer agents (Mn=350, 750 and 2000 g/mol). The presence of copolymers inhibited the crystal growth of calcium oxalate possibly through adsorption onto the active growth sites for crystal growth due to the charge and hydrophilic effects. Copyright (C) 2006 John Wiley & Sons, Ltd.
Keywords: polyelectrolytes; block copolymers; radical polymerization; calcium oxalate; crystallization; TRANSFER RADICAL POLYMERIZATION; CRYSTAL-GROWTH RATE; SULFATE DIHYDRATE; PRECIPITATION; ADDITIVES; ARCHITECTURE; COMPLEXES; COPOLYMER; PROTEINS; POLYMERS; Polymer Science